Exploring non-thermal plasma technology for microalgae removal - Tanzooei, Ali Mohammad; Karimi, Javad; Taghvaei, Hamed (Ecotoxicology and environmental safety, 2024)
The global population and economic development surge has substantially increased water demand, resulting in heightened sewage and pollutant generation, posing environmental hazards. Addressing this challenge necessitates the implementation of efficient and cost-effective water reclamation methods. Non-thermal plasma technology (NTP) has emerged as a promising solution, garnering attention for its superior efficiency compared to alternatives. While existing studies have predominantly focused on energy efficiency and pollutant removal, limited research has delved into the biological removal aspect, particularly concerning algae. This study utilized a dielectric barrier plasma diffuser to eliminate Spirulina microalgae (Spirulina platensis) from wastewater solutions, demonstrating higher algae removal and superior mass transfer compared to alternative plasma methods. The effect of sample volume, input voltage and power, flow rate, and initial solution concentration on the algae removal was investigated. Investigation of operational parameters revealed the best condition resulting in a 98 % removal rate and 20 g/kWh energy efficiency. The best conditions for the removal of Spirulina microalgae were considered in a sample volume of 50 mL, a voltage of 7.6 kV, a flow rate of 700 mL/min, and an initial solution concentration of 1280 mg/liter. Scanning Electron Microscope (SEM) images illustrated the impact of active species on cell structure, leading to the destruction of spiral form and loss of reproductive ability. The study underscores the potential of NTP for efficient algae removal and identifies key active species involved in the process. The removal of Spirulina microalgae was attributed to a combination of singlet oxygen (1O2), hydroxyl radicals, and ozone. •Achieving higher removal efficiency and superior mass transfer compared to alternative plasma methods.•Achieving a remarkable removal rate of 98 % alongside an energy efficiency of 20 g/kWh.•Loss of spiral shape and inability of microalgae to reproduce.•Identification of singlet oxygen (1O2), hydroxyl radicals, and ozone as key reactive species responsible for algae removal.